Simultaneous Bilateral Cochlear Implantation for a 6-Month Child with a History of Meningitis - Kh. M. Diab; N. A. Daikhes; A. R. Siraeva; D. S. Kondratchikov; O. A. Pashchinina; D. P. Polyakov ("Paediatrician" Publishers LLC, 2015)
The article presents the first case of simultaneous bilateral cochlear implantation for a 6-month child with IV degree sensorineural hearing loss after meningocephalitis in Russia. Despite partial ossification of the cochlear basal turns, the early timing of implantation allowed to fully implant active electrodes to both ears. The simultaneous bilateral cochlear implantation in young children, who had meningitis, is a minimally invasive and highly efficient procedure with good long-term results of oral-aural after-care.